2019
DOI: 10.4018/978-1-5225-7470-5.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Using Learning Analytics to Improve Engagement, Learning, and Design of Massive Open Online Courses

Abstract: Academic research in the past decade has indicated that using data and analyzing learning in curriculum design decisions can lead to improved student performance and student success. As learning in many instances has evolved into the flexible format online, anywhere at any time, learning analytics could potentially provide impactful insights into student engagement in massive open online courses (MOOCs). These may contribute to early identification of “at risk” participants and provide MOOC facilitators, educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…The results indicated that the CLDLA model has a positive impact on learners' engagement. This is in line with previous studies highlighting the positive impacts of LA on engagement (e.g., Calonge et al, 2019;Chen et al, 2018;Toro-Troconis et al, 2019;Vytasek et al, 2020). Although previous studies confirmed that LA plays a positive role in improving students engagement, they also expressed concerns that LA implications for students' engagement could be threatened by LA technological determinism if these data findings have not been viewed and interpreted through a wider pedagogical and learning lens (Knight et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results indicated that the CLDLA model has a positive impact on learners' engagement. This is in line with previous studies highlighting the positive impacts of LA on engagement (e.g., Calonge et al, 2019;Chen et al, 2018;Toro-Troconis et al, 2019;Vytasek et al, 2020). Although previous studies confirmed that LA plays a positive role in improving students engagement, they also expressed concerns that LA implications for students' engagement could be threatened by LA technological determinism if these data findings have not been viewed and interpreted through a wider pedagogical and learning lens (Knight et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…However, one of the critical challenges is the lack of attention to pedagogical and theoretical foundations in the use of LA (Banihashem et al, 2018(Banihashem et al, , 2019Gašević et al, 2016;Knight et al, 2014;Wiley et al, 2020;Wise, 2014). In previous studies, LA was mostly used as a tool to support and inform the design of learning, engagement, and self-regulation (see Calonge et al, 2019;Chen et al, 2018;Heller, 2020;Holmes et al, 2019;Ifenthaler et al, 2018;Kim et al, 2018;Persico & Pozzi, 2015;Roll & Winne, 2015;Toro-Troconis et al, 2019;Viberg et al, 2020;Winne, 2017). However, it lacks sound theory-oriented pedagogy (Wiley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Second, previous experience, data, and the untapped potential of social media. Calonge et al (2019) advocated that "purposeful learning and curriculum design decisions are a fundamental means to enhance participant engagement, motivation and performance in an online course" (p. 100). Academics need to harness data, analyze previous experience (their own and students') and satisfaction with courses facilitated online, reflect, generate actionable insights, and make decisions based on this information (Stephens et al, 2021).…”
Section: Engagement In the Hyflex Modalitymentioning
confidence: 99%
“…DAWSON, 2015). No entanto, a maioria dos cursos on-line segue uma abordagem conservadora, com uma sequência um pouco fixa de: ler conteúdo, assistir a uma palestra em vídeo, interagir em fóruns e fazer uma avaliação automática (CALONGE et al, 2019). A falta de interação humana e o feedback individual foram sugeridos como as principais limitações no design do MOOC (YOUSEF et al, 2014).…”
Section: Discussão E Conclusõesunclassified